WorldFish Carp Genetic Improvement Program Pond Books 2024 - Shanta, Sirajum Monira; Akhter, Md; Hamilton, Matthew (2025)
Data on inputs, environmental parameters and sampling of ponds at the WorldFish Carp Genetic Improvement Program Facility in Bangladesh